Beyonce : i... am Sasha Fierce (Sony Music Entertainment, 2008)
Beyonce's third studio release is split between two discs: the slower, R & B/jazz-infused I Am Beyonce, and the more upbeat, dance-oriented I Am Sasha, which features Beyonce performing as her alter ego, Sasha Fierce.